2005
DOI: 10.1196/annals.1336.018
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Germ Cell Maturation

Abstract: Spermatogenesis requires progression of germ line stem cells through a precisely ordered differentiation pathway to form spermatozoa. Diverse and dynamic signals from the transforming growth factor-beta (TGF-beta) superfamily influence many stages of germ cell development. For example, interactions between several TGF-beta superfamily ligands (bone morphogenetic proteins, activin, and glial-derived neurotrophic growth factor [GDNF]) appear to govern the onset of spermatogenesis, and we are exploring how germ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
0
20
1
Order By: Relevance
“…In addition, activin A dosage affects growth of the fetal murine epididymis between E15.5 and E19.5 [13], and has the capacity to influence Sertoli cell proliferation and cord expansion in the mouse [14]. Our previous preliminary results [15] indicated that activin contributed to the suppression of germ cell numbers in the fetal testis, but the timing and mechanism by which this occurred were unknown.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, activin A dosage affects growth of the fetal murine epididymis between E15.5 and E19.5 [13], and has the capacity to influence Sertoli cell proliferation and cord expansion in the mouse [14]. Our previous preliminary results [15] indicated that activin contributed to the suppression of germ cell numbers in the fetal testis, but the timing and mechanism by which this occurred were unknown.…”
Section: Introductionmentioning
confidence: 90%
“…These observations suggest a dual role of activin regulation on gonocyte development, where a reduction in local activin concentration is required for gonocytes to exit from their state of G1 arrest, while subsequent elevation in activin levels suggests a role in promoting gonocyte proliferation. The role of activin as an inducer of mitotic arrest in gonocytes is evident in the elevated gonocyte numbers in testes of newborn mice lacking the b A subunit (Inhba K/K ; Loveland et al 2005). Subsequently, the role of activin as a mitogen is reflected in a study of 3-day-old rat testis fragment cultures, which showed that increased activin levels induced the proliferation of gonocytes (Meehan et al 2000).…”
Section: Inhibins and Fsh In Mouse Testismentioning
confidence: 99%
“…line-derived neurotrophic factor, GDNF, (5)(6)(7); activin A and bone morphogenetic protein 4, BMP4, (8,9)], Leydig or peritubular myoid cells [colony-stimulating factor (CSF) 1, CSF1 (10 -11)], contribute to the niche homeostasis, and influence the balance between SSC self-renewal and differentiation (4). It is possible that yet unknown factors participate in regulating germ cell proliferation/ differentiation or that known factors exert yet unknown functions in the testis.…”
mentioning
confidence: 99%